Antiviral Actions of 25-Hydroxycholesterol in Fish Vary With the Virus-Host Combination - Adamek, Mikolaj; Davies, Jonathan; Beck, Alexander; Jordan, Lisa; Becker, Anna M.; Mojzesz, Miriam; Rakus, Krzysztof; Rumiac, Typhaine; Collet, Bertrand; Brogden, Graham; Way, Keith; Bergmann, Sven M.; et al. (Frontiers in Immunology, 2021)
Cholesterol is essential for building and maintaining cell membranes and is critical for several steps in the replication cycle of viruses, especially for enveloped viruses. In mammalian cells virus infections lead to the accumulation of the oxysterol 25-hydroxycholesterol (25HC), an antiviral factor, which is produced from cholesterol by the cholesterol 25 hydroxylase (CH25H). Antiviral responses based on CH25H are not well studied in fish. Therefore, in the present study putative genes encoding for CH25H were identified and amplified in common carp and rainbow trout cells and an HPLC-MS method was applied for determination of oxysterol concentrations in these cells under virus infection. Our results give some evidence that the activation of CH25H could be a part of the antiviral response against a broad spectrum of viruses infecting fish, in both common carp and rainbow trout cells in vitro. Quantification of oxysterols showed that fibroblastic cells are capable of producing 25HC and its metabolite 7α,25diHC. The oxysterol 25HC showed an antiviral activity by blocking the entry of cyprinid herpesvirus 3 (CyHV-3) into KFC cells, but not spring viremia of carp virus (SVCV) or common carp paramyxovirus (Para) in the same cells, or viral haemorrhagic septicaemia virus (VHSV) and infectious pancreatic necrosis virus (IPNV) into RTG-2 cells. Despite the fact that the CH25H based antiviral response coincides with type I IFN responses, the stimulation of salmonid cells with recombinant type I IFN proteins from rainbow trout could not induce ch25h_b gene expression. This provided further evidence, that the CH25H-response is not type I IFN dependent. Interestingly, the susceptibility of CyHV-3 to 25HC is counteracted by a downregulation of the expression of the ch25h_b gene in carp fibroblasts during CyHV-3 infection. This shows a unique interplay between oxysterol based immune responses and immunomodulatory abilities of certain viruses.